Factors Influencing Employee Job Satisfaction: Literature Review - Syahril, Muhammad (International Journal of Business, Technology and Organizational Behavior (IJBTOB), 2025)
Abstract: Previous research has the function of strengthening the theory and facts regarding the relationship or influence between the variables studied. This article examines the factors that influence employee job satisfaction, namely: work-life balance, organizational culture and leadership style, a study of Human Resource Management literature. Discussion of this theme is considered important considering the many parties who have studied the same or relevant discussion, because they believe in the importance of understanding how to create job satisfaction for employees and what factors influence it. The results of this literature review article are: 1) Work-life balance influences job satisfaction; 2) Organizational culture influences job satisfaction; and 3) Leadership style influences job satisfactionKeywords: Job Satisfaction, Work-life Balance, Organizational Culture, Leadership Style